2017
DOI: 10.1590/s1806-37562016000000339
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer: changes in histology, gender, and age over the last 30 years in Brazil

Abstract: Objective:To describe the trends in tumor histology, gender and age among patients with non-small cell lung cancer (NSCLC) treated with lung resection. The histology of lung cancer has changed in developed countries, and there is still little information available on the topic for developing countries. Methods:This was a retrospective study of 1,030 patients with NSCLC treated with lung resection between 1986 and 2015 at a university hospital in southern Brazil. Differences in histology, stage, and type of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
0
12
0
8
Order By: Relevance
“…Many studies have analyzed the related factors affecting the survival and prognosis of NSCLC patients, such as tobacco prevalence, sex, age, TNM stage and histopathological classification. 12,13 In addition, the choice of treatment regimen and patient's compliance are also prognostic factors in patients with NSCLC. Jayia 14 found in a retrospective study that compliance can improve the prognosis of patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have analyzed the related factors affecting the survival and prognosis of NSCLC patients, such as tobacco prevalence, sex, age, TNM stage and histopathological classification. 12,13 In addition, the choice of treatment regimen and patient's compliance are also prognostic factors in patients with NSCLC. Jayia 14 found in a retrospective study that compliance can improve the prognosis of patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A previous report found that percutaneous CT-guide biopsy had a diagnostic yield of 93%, higher than that of bronchoscopy biopsy at 75%. Additionally, the proportion of the more commonly regarded centrally located squamous cell carcinoma has decreased over the past 30 years, from 49.6% to 34.8% [21]. Moreover, traditionally recognized centrally located squamous cell carcinoma has been reported to consist of more than 62% of squamous cell carcinoma [22].…”
Section: Discussionmentioning
confidence: 99%
“…The profile found is consistent with what has been identified in recent years in developed countries, as well as in Brazil. Even though it is an underdeveloped country, due to the great efforts in anti-smoking actions, we have seen the altered epidemiology of lung cancer in recent years, with an increase in the incidence of adenocarcinoma and a decrease in squamous cell carcinoma according to Tsukazan et al [ 15 ].…”
Section: Discussionmentioning
confidence: 99%